Optical generation of the first and second sounds in superfluid 3He-4He solutions - Salikhov, T. Kh. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
An optical method of generation of the first and second sounds in superfluid 3He - 4He solutions is proposed. The method is based on illumination by amplitude-modulated laser beam with wavelength corresponding to a region of absorption. Numerical calculations of pressure and temperature as a function of time are carried out. It was found that the presence of 3He isotopes in the solution provides strong coupling between these parameters and, as a result, the waves of the first sound involve oscillations of the temperature, while the waves of the second sound involve oscillations of the pressure.